2019
DOI: 10.1002/ehf2.12544
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril/valsartan in heart failure and end‐stage renal insufficiency

Abstract: The aim of this report is to describe the feasibility and tolerability of medical treatment with sacubitril/valsartan in a patient treated with hemodialysis. We describe the case of a 67-year-old man with heart failure with reduced ejection fraction due to an ischemic cardiomyopathy and renal insufficiency undergoing hemodialysis. Because of worsening heart failure with no other therapeutic options, a treatment with sacubitril/valsartan was started. Although this patient had a very low systolic blood pressure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 5 publications
1
15
0
1
Order By: Relevance
“…What is interesting, it is also proven that the therapy with valsartan significantly increases the long-term quality of life in patients with chronic heart failure [74], which is a result of biochemical, echocardiographic, and clinical improvements [75]. Simultaneously, the drug remains safe in patients with many comorbidities, especially in chronic kidney disease [76]. In patients with hypertension, the use of valsartan is also associated with the reduction of the risk of organ complications, including left ventricular hypertrophy [77,78].…”
mentioning
confidence: 99%
“…What is interesting, it is also proven that the therapy with valsartan significantly increases the long-term quality of life in patients with chronic heart failure [74], which is a result of biochemical, echocardiographic, and clinical improvements [75]. Simultaneously, the drug remains safe in patients with many comorbidities, especially in chronic kidney disease [76]. In patients with hypertension, the use of valsartan is also associated with the reduction of the risk of organ complications, including left ventricular hypertrophy [77,78].…”
mentioning
confidence: 99%
“…After initiation of sacubitril/valsartan, there was a symptomatic improvement with a clear reduction NT-proBNP, accompanied by a decrease in filling pressures [11] A retrospective study analysed the clinical and laboratory data of 23 HFrEF patients, found that sacubitril/valsartan could reduce the hsTnT (high-sensitive troponin) and sST2 (soluble ST2) levels and improve LVEF in HFrEF patients with ESRD, which is the first study to show the effectiveness and safety of sacubitril/valsartan in ESRD patients with HFrEF [10].…”
Section: Case Reports In Clinical Medicinementioning
confidence: 96%
“…There have been a few studies published on the use of sacubitril/valsartan in patients with stage 4 or 5 CKD, or There is a paucity of data on the evidence of ARNI in patients with ESRD on maintenance dialysis. Heyse et al [56] presented a case report of a 67-year-old man with HFrEF due to ischemic cardiomyopathy and renal insufficiency undergoing hemodialysis, who tolerated a moderate dose of 49/51 mg twice daily, and finally showed symptomatic improvement with a reduction in HF biomarkers and left ventricular filling pressure. Only one study evaluated the use of sacubitril/valsartan in patients with HFrEF and ESRD, which showed that sacubitril/valsartan reduced cardiac biomarkers and improved LVEF; the most common adverse event was hypotension, which was corrected with down-titration of the drug dosage [57].…”
Section: Efficacy and Safety Of Angiotensin Receptorneprilysin Inhibitor In Advanced Chronic Kidney Diseasementioning
confidence: 99%